Disrupting cell death: ferroptosis and pyroptosis inhibition in hepatic ischemia-reperfusion injury via modulation of GPX4 and cGAS pathways by deferoxamine and octreotide - Tawfiq, Rasha A.; Attia, Yasmeen M.; Sleem, Hameis M.; El-Sayed Ghoneim, Mai (Frontiers in Pharmacology, 2025)
Hepatic ischemia-reperfusion injury (HIRI) is a significant complication of liver transplantation, often precipitating postoperative liver dysfunction/failure. Given the rising global prevalence of end-stage liver disease, which necessitates liver transplantation, protecting against HIRI is crucial. Here, we investigated the effects of octreotide (OCT), a pyroptosis inhibitor, and deferoxamine (DEF), a ferroptosis suppressor, individually and combined in the HIRI model. Their impact on cyclic GMP-AMP synthase/stimulator-of-interferon (cGAS/STING) genes and glutathione peroxidase 4 (GPX4) activity was explored. Male rats (n = 4–5) were subjected to 30 min ischemia followed by 3 h reperfusion and treated with OCT (75 μg/kg; 30 μg/kg, i.p. & 45 μg/kg, s.c.), DEF (200 mg/kg, i.p.), or their combination 30 min prior to ischemia. DEF and the combined therapy alleviated HIRI histopathologically compared to OCT, while all treatments improved liver function. Ferroptosis suppression was noticeable with DEF and the combined regimen, likely via GPX4 activation and cyclooxygenase 2 (COX2) inhibition. All treatments displayed anti-inflammatory activity through suppressing toll-like receptor 4 (TLR4)/nuclear factor-kappa-B (NFkB) axis and pyroptosis. The combination, however, lacked anti-pyroptotic activity. These alterations paralleled cGAS downregulation, independent of STING modulation. Collectively, DEF conferred superior hepatoprotection compared to OCT, primarily due to its antioxidant and anti-inflammatory activities. Combinatorial therapy amplified the modulation of GPX4, COX2, and TLR4/NFκB without additive antipyroptotic activity.